(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
The railway culture has been a space for the reproduction of hegemonic masculinity in practically the entire world. In Chile, for more than 160 years, the State Railway Company was established in a secularized space in which transversely, in all its states, the categories of an exclusive and closed masculinity group were reproduced. The conditions of this process of gender construction in the company of the most important State in the country for territorial articulation and connectivity are analyzed. Its relevance is marked by being the model institution in Fordist industrialization from the mid-nineteenth century until its decline at the end of the twentieth century. The areas of socialization of masculinities in the railway world are characterized in the context of a culture that makes feminine invisible by relegating it to a vicarious alterity